Effects of nateglinide and rosiglitazone on pancreatic alpha- and beta-cells, GLP-1 secretion and inflammatory markers in patients with type 2 diabetes: randomized crossover clinical study. Issue 1 (December 2016) - Tostes, Glauce; Cunha, Maria; Fukui, Rosa; Correia, Márcia; Rocha, Dalva; Santos, Rosa; Silva, Maria
Abstract Background To compare the effects of nateglinide and rosiglitazone on inflammatory markers, GLP-1 levels and metabolic profile in patients with type 2 diabetes (DM2). Methods A prospective study was performed in 20 patients with DM2, mean age 51.82 ± 8.05 years, previously treated with dietary intervention. Participants were randomized into rosiglitazone (4–8 mg/day) or nateglinide (120 mg 3 times a day) therapy. After 4 months, the patients were crossed-over with 8 weeks washout period to the alternative treatment for an additional 4-month period on similar dosage schedule. The following variables were assessed before and after 4 months of each treatment period: (1) a test with a standardized 500 calories meal for 5 h including frequent measurements of glucose, insulin, glucagon, proinsulin, GLP-1, free fat acids (FFA), and triglycerides levels was obtained. The lipid profile and HbA1 levels were measured at fasting. (2) Haemostatic and inflammatory markers: platelet aggregation, fibrinogen, PAI-1 activity, C reactive protein (CRP), IL-6, TNF-α, leptin, sICAM and TGFβ levels. Results Both therapy decreased blood glucose levels under the postprandial curve but neither affected glucagon and GLP-1 levels. Nateglinide was associated with higher insulin and pro-insulin secretion, but similar pro-insulin/insulin ratio when compared with rosiglitazone. Only rosiglitazone decreased Homa β, PAI-1 activity, CRP, fibrinogen, TGFβ, FFA and triglyceride levels. Conclusions Nateglinide and rosiglitazone were effective in improving glucose and lipid profile and β cell function, but rosiglitazone afforded a better anti-inflammatory effect. No drug restored alpha cell sensitivity or changed GLP-1 levels. Maintenance of haemostatic factors, inflammatory factors and glucagon levels can be related to the continuously worsening of cardiovascular function and glucose control observed in DM2.